Race and a Transnational Reproductive Caste System: Indian Transnational Surrogacy. (2014) - Banerjee, Amrita
Abstract : When it comes to discourses around women's labor in global contexts, we need feminist philosophical frameworks that take the intersections of gender, race, and global capitalism seriously in order to arrive at a comprehensive understanding of women's lives within global processes. Women of color feminist philosophy can bring much to the table in such discussions. In this essay, I theorize about a concrete instance of global women's labor: transnational commercial gestational surrogacy. By introducing a "racialized gender" analysis into the philosophical debate on this issue, I argue that women's reproductive labor is becoming increasingly stratified within the global economy along racial and other lines. This paves the way for a "transnational reproductive caste system, " which ends up reifying various social hierarchies and sustaining existing global inequities. I aim to expose the kind of violence that surrogates experience due to such stratification as women of color in a transnational space. I discuss how discourses of race and existing racial hierarchies play out in international surrogacy and ways in which these, and indeed, the very category of "woman of color" get complicated in international contexts when they intermingle with other localized social forms and global inequities. For the purposes of my argument, I engage several insights from feminist of color Dorothy Roberts's work on race and reproductive technologies in the US.